Sport harassment in the eyes of Hong Kong youth swimmers - Fung, L.; Tsai, E.; Chow, L. P. Y.; Carre, A. (International Journal of Sport & Health Science, 2004)
In this study, sport harassment is defined as harassment situated in sport. The aims of the study were to identify behaviors considered to be a form of sport harassment in the eyes of Hong Kong youth swimmers and to understand the prevalence of sport harassment sustained by them. Given that some forms of sport harassment are more offensive than others, the study also aims to identify those forms which youth swimmers find more offensive.